Spectral features of a single type III burst in the frequency range of 10–70 MHz - Melnik, Valentin; Brazhenko, Anatolii; Dorovskyy, Vladimir; Frantsuzenko, Anatolii; Shevchuk, Mykola; Yerin, Sergii; Bubnov, Igor (Frontiers in Astronomy and Space Sciences, 2024)
Spectral properties of a single type III burst in the wide frequency band from 10 to 70 MHz are studied in detail. It is shown that electrons corresponding to different levels of type III emission move with different velocities. Moreover, these electron velocities decrease from the maximum value, which corresponds to the 0.1 level of the maximum type III flux at its front, to the minimum value, corresponding to the 0.1 level of the maximum type III flux at its back. The velocity of electrons corresponding to the maximum type III flux was approximately 0.31 c. This value equals 0.6 of maximum velocity, and, namely, it was predicted by the gas dynamic theory of electron propagation through the coronal plasma. In addition, we adduce arguments that the type III radio emission is the harmonic emission. In supposition that type III electrons move through the Newkirk coronal plasma, we find electron velocities for every level of the type III burst. The duration dependence on frequency obtained from the observations is close to Elgaroy–Lingstad dependence. We discuss the contribution of electron velocity dispersion to the type III burst duration. In addition, we derived type III flux dependence on frequency in the frequency bands of 10–33 MHz and 33–62 MHz.